2010
DOI: 10.5194/acp-10-1671-2010
|View full text |Cite
|
Sign up to set email alerts
|

Source-receptor relationships for airborne measurements of CO<sub>2</sub>, CO and O<sub>3</sub> above Siberia: a cluster-based approach

Abstract: Abstract. We analysed results of three intensive aircraft campaigns above Siberia (April and September 2006, August 2007) with a total of ∼70 h of continuous CO 2 , CO and O 3 measurements. The flight route consists of consecutive ascents and descents between Novosibirsk (55 • N, 82 • E) and Yakutsk (62 • N, 129 • E). We performed retroplume calculations with the Lagrangian particle dispersion model FLEX-PART for many short segments along the flight tracks. To reduce the extremely rich information on source r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 45 publications
4
42
0
Order By: Relevance
“…Boreal forest fires are also an important source of PAN and, due to their proximity to the Arctic, plumes can be transported to high latitudes during the spring and summer months (Brock et al, 2011;Singh et al, 2010). Whilst little O 3 production appears to occur close to boreal fires (Alvarado et al, 2010;Paris et al, 2010), several recent studies have shown O 3 production downwind from boreal fires in the Arctic during the summer months (Wespes et al, 2012;Parrington et al, 2012;Thomas et al, 2013). Nevertheless, O 3 production is higher in air masses influenced by anthropogenic emissions.…”
Section: Arcticmentioning
confidence: 97%
“…Boreal forest fires are also an important source of PAN and, due to their proximity to the Arctic, plumes can be transported to high latitudes during the spring and summer months (Brock et al, 2011;Singh et al, 2010). Whilst little O 3 production appears to occur close to boreal fires (Alvarado et al, 2010;Paris et al, 2010), several recent studies have shown O 3 production downwind from boreal fires in the Arctic during the summer months (Wespes et al, 2012;Parrington et al, 2012;Thomas et al, 2013). Nevertheless, O 3 production is higher in air masses influenced by anthropogenic emissions.…”
Section: Arcticmentioning
confidence: 97%
“…Arctic tropospheric ozone is significantly influenced by long-range import of ozone and precursors from midlatitude sources as well as by boreal wildfires Wespes et al, 2012;Paris et al, 2010b;Vivchar et al, 2009). The role of biomass burning emissions in the ozone budget in high latitudes remains controversial.…”
Section: Main Pollutantsmentioning
confidence: 99%
“…More recently, LPDMs have been used for various research applications at a regional scale (Lin et al, 2003(Lin et al, , 2006(Lin et al, , 2007Paris et al, 2010;Warneke et al, 2009). When applying an LPDM for global analysis, a long-term integration is required (see Stohl et al, 2010), although this approach is not as computationally efficient as that of Eulerian models.…”
Section: Introductionmentioning
confidence: 99%